Cardiovascular Imaging in Pregnancy: Valvulopathy, Hypertrophic Cardiomyopathy, and Aortopathy - Ismail, Haneen; Bradley, Andrew J.; Lewis, Jannet F. (Frontiers in Cardiovascular Medicine, 2022)
Pregnancy is associated with profound hemodynamic changes that are particularly impactful in patients with underlying cardiovascular disease. Management of pregnant women with cardiovascular disease requires careful evaluation that considers the well-being of both the woman and the developing fetus. Clinical assessment begins before pregnancy and continues throughout gestation into the post-partum period and is supplemented by cardiac imaging. This review discusses the role of imaging, specifically echocardiography, cardiac MRI, and cardiac CT, in pregnant women with valvular diseases, hypertrophic cardiomyopathy, and aortic pathology.